화학물질 관련법에 대한 입법평론 - 홍완식 (입법학연구, 15(1), 2018)
2012년 구미 불산사고 등 대형 화학사고가 발생하지 않았다면 우리나라에서는 아직도 「화학물질관리법」과 「화학물질의 등록 및 평가에 관한 법」 등에 대한 법령개선 혹은 법령정비는 이루어지지 않았을 가능성이 크다. 그리고 화학물질에 대한 안전관리는 이미 국가 내적인 문제가 아니라 국가 간의 문제로 확대되었으며, 이제는 화학물질의 통제와 교역은 인류가 공동으로 대처하여야 하는 국제적인 문제로 인식되고 있다. 국가는 국민의 안전에 더욱 많은 정책적 배려를 하여야 한다. 국회는 화학물질로부터 안전하게 법령을 개선하여야 하며 이러한 법령은 집행부에 의하여 엄격히 집행되어야 하고, 화학물질로부터의 안전을 위한 법령의 해석과 적용에 있어서도 법원은 국민의 안전권 확보에 비중을 두어야 한다. 제조업자는 제조물의 안전성을 철저히 검증하고 조사･연구를 통하여 발생 가능성 있는 위험을 제거･최소화하여야 하며, 안전성이 충분히 확보될 정도로 그 위험이 제거･최소화되었다고 확인되기 전에는 그 화학제품을 유통시키지 말아야 한다. 입법･집행･사법 전반을 포함하여 국가의 최우선적 의무는 국민의 건강과 생명을 지키는 일이다. 국내의 화학물질 규제강화에 따른 산업계의 비용증가와 경쟁력 약화 등에 대한 우려가 있다. 그러나 도처에 존재하고 사용되는 화학물질로부터 안전하기 위해서는, 법규위반에 대한 처벌이 낮고 사업장의 안전관리가 미흡하다는 점이 지속적으로 지적되고 있다. 따라서 화학물질관련 국제기준이 화학물질 관련 국제시장의 진입 등에 중요한 관건이 되고 있는 현실에 비추어 규제비용은 국제경쟁력을 위한 투자라고 인식할 필요가 있다. 화학물질의 관리와 규제는 양면성을 지니고 있다. 화학물질의 위험과 사고로부터 생명을 지키고 환경을 보호하기 위해서는 엄격한 관리 및 규제가 필요하다. 그러나 지나친 관리 및 규제는 산업계의 생산력과 경쟁력을 위축시킬 우려가 있다는 점을 고려하여 화학물질 관련 입법정책을 수립하여야 한다. The chemicals means any element, compound, and chemicals obtained as a result of an artificial reaction therewith, and any chemicals chemically transformed, extracted, or refined from chemicals existing in nature. The restricted chemicals means chemicals recognized as having a high risk if they are used for specific purposes, which are publicly notified by the Minister of Environment following consultations with the heads of relevant central administrative agencies and deliberations by the Chemicals Assessment Committee on Registration, Evaluation, etc. of Chemicals to prohibit the manufacture, importation, sale, keeping, storage, transport, or use of such chemicals for such purposes. The prohibited chemicals means chemicals recognized as having a high risk if they are used for specific purposes, which is designated and publicly notified by the Minister of Environment following consultations with the heads of relevant central administrative agencies and deliberations by the Chemicals Assessment Committee on Registration, Evaluation, etc. of Chemicals to prohibit the manufacture, importation, sale, keeping, storage, transport or use of such chemicals for all purposes. The hazardous chemical substance means any of the toxic substances, substances subject to permission, restricted substances, prohibited substances, and other chemical substances that pose or are likely to pose hazards or risks. The purpose of the Chemicals Control Act is to prevent risks posed by chemicals to people's health and the environment and protect the lives and property of the people or the environment from chemicals by properly controlling chemicals and promptly responding to accidents that occur due to chemicals. The purpose of the Act on regislation, evaluation of chemicals is to protect public health and the environment by providing for matters concerning the registration of chemical substances, the review and assessment of the hazards and risks of chemical substances and products containing hazardous chemical substances, and the designation of hazardous chemical substances and by producing and utilizing information on chemical substances. KCI Citation Count: 3